ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN JASA PENGIRIMAN BARANG DIKANTOR PUSAT LION PARCEL PONTIANAK - Saparudin Saparudin; Aminuyati Aminuyati; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine what factors affect the demand for goods delivery services at Lion Parcelhead to office Pontianak’s. the reseach methoed used is factor analysis. The data used are primary data. The sample studied was 124 respondents. The number of statements analyzed was 31 statements and the data were processed using faktor analysis with the SPSS version 22 application. The result showed that of the 31 statements analyzed using the factor analyzed model, there were 7 factors that were formed, namely (1) Factor Tariff with variance value 33.093%, (2) the Faktor Of Responsivensess with variance value 9.221%, (3) the Factor of Empathy with variance value 7.150%, (4) the Factor Of Advertising with variance value 5.053%, (5) the Factor of Reliability with variance value 3.985%, (6) the Factor of Expectation with variance value 3.842%, and (7) Promotion Factor with variance value 3.583%. The cumulative percentage of the variance of extracted factors is 65.926%, which means that the result of this study are able to explain the factors that influence the demand for goods delivery services athead office Lion Parcel Pontianak of 65.926 % an rest is influenced by toher factos.Keywords: Demand, Delivery Service, Lion Parcel.